Pemanfaatan Lahan Eks-Tambang Batubara Guna Meningkatkan Pendapatan Ekonomi Masyarakat dan Pembelajaran untuk Siswa SMA Negeri 1 Loa Janan - Risma Nurul Pujiasih; Suryaningsi Suryaningsi; Endang Herliah (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Sustainable use of ex-mining land is an important aspect of sustainable development. By teaching students about reusing mined land, we can help develop a generation that cares more about the environment. The aim of this research is to explore the potential for using ex-coal mining land to increase the economic income of local communities and also for learning for students at SMA Negeri 1 Loa Janan. The type of research used is descriptive qualitative, data analysis techniques are data collection, data reduction, and data conclusion. The research results show that ex-coal mining land can help increase the economic income of local communities and can be an effective teaching material in PKN learning. Utilizing ex-coal mining land for economic activities has great potential to increase the income of local communities. This research proves that the use of ex-coal mining land as enrichment material for PKN teaching materials is effective in increasing understanding of PKN teaching materials for students at SMA Negeri 1 Loa Janan.